Determination of solar window for Baghdad city using pv system program (Baghdad Science Journal, 2025)
Been using a pv system program to determine the solar window for Baghdad city . the solar window for any location can be determine by deviating left and right from the geographical south as well as deviation according to the amount of tilt angle with the horizon for fixed panel so that will not change the average of solar radiation incident over the whole year and this lead to help in the process of installation of fixed solar panel without any effect on annual output .the range of solar window for Baghdad city between two angles ( -8 - +8 ) degrees left to right of the geographical south and tilt angle that allowed for the horizon range between angles (21- 30) degrees so that the amount of solar radiation that falling on the solar panel in this range of fixed angles about5.6 kw.h/m2 yearl.